ORGANISASI DAN KOMITMEN AFEKTIF RESPONSIBLE LEADERSHIP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PT. PLN (PERSERO) UP 3 - Mhd Febryansah; H.M Hermansyur; Rizky Putra (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2022)
This research was conducted in PT. PLN (Persero) UP 3 Binjai with the aim of research to determined the partial and simultaneous effected of organizational support and affective commitment which influenced by responsible leadership and organizational citizenship behavior. The population were employees who worked in the company in 2021 as many as 125 employees, sampling itwas carried out with census sample so that the total sample were 125 respondents. Sources of data using primary data and data collection techniques with literature study, observation and questionnaires. The data analysis technique used data quality test, classical assumption test, multiple linear regression and hypothesis testing. Based on the results of the study, it showed that partially organizational support has significant effected on responsible leadership and organizational citizenship behavior, while partially affective commitment did not have significant effected on responsible leadership and organizational citizenship behavior. Keywords: Organizational Support, Affective Commitment, Responsible Leadership, Organizational Citizenship Behavior